TEACHING ENGLISH THROUGH LITERATURE - Azizova Makharam Rashitovna (European Science Publishing, 2025)
This article is devoted to the use of literature in teaching English. It is spoken in the article, that the role of literature in the foreign language curriculum was unquestioned. It was believed that learners could only appreciate a language through the study of its highest from of expression. Literature was seen as the only way to get to know a nation's culture. Literature serves as excellent source material for students and also teachers. It can be selected as a wide range of texts from prose, drama, and poetry from different centuries.
Keywords: Literature, topic, collection, reading, dictionary vocabulary, authors, interpretation.